Stimulation of homologous recombination in plants expressing heterologous recombinases - Barakate, Abdellah (BMC Plant Biol, 2020)
BACKGROUND: Current excitement about the opportunities for gene editing in plants have been prompted by advances in CRISPR/Cas and TALEN technologies. CRISPR/Cas is widely used to knock-out or modify genes by inducing targeted double-strand breaks (DSBs) which are repaired predominantly by error-prone non-homologous end-joining or microhomology-mediated end joining resulting in mutations that may alter or abolish gene function. Although such mutations are random, they occur at sufficient frequency to allow useful mutations to be routinely identified by screening. By contrast, gene knock-ins to replace entire genes with alternative alleles or copies with specific characterised modifications, is not yet routinely possible. Gene replacement (or gene targeting) by homology directed repair occurs at extremely low frequency in higher plants making screening for useful events unfeasible. Homology directed repair might be increased by inhibiting non-homologous end-joining and/or stimulating homologous recombination (HR). Here we pave the way to increasing gene replacement efficiency by evaluating the effect of expression of multiple heterologous recombinases on intrachromosomal homologous recombination (ICR) in Nicotiana tabacum plants. RESULTS: We expressed several bacterial and human recombinases in different combinations in a tobacco transgenic line containing a highly sensitive β-glucuronidase (GUS)-based ICR substrate. Coordinated simultaneous expression of multiple recombinases was achieved using the viral 2A translational recoding system. We found that most recombinases increased ICR dramatically in pollen, where HR will be facilitated by the programmed DSBs that occur during meiosis. DMC1 expression produced the greatest stimulation of ICR in primary transformants, with one plant showing a 1000-fold increase in ICR frequency. Evaluation of ICR in homozygous T2 plant lines revealed increases in ICR of between 2-fold and 380-fold depending on recombinase(s) expressed. By comparison, ICR was only moderately increased in vegetative tissues and constitutive expression of heterologous recombinases also reduced plant fertility. CONCLUSION: Expression of heterologous recombinases can greatly increase the frequency of HR in plant reproductive tissues. Combining such recombinase expression with the use of CRISPR/Cas9 to induce DSBs could be a route to radically improving gene replacement efficiency in plants.